ANALISIS BENEISH RATIO INDEX: BERPERANKAH DALAM MENDETEKSI KECURANGAN PADA PELAPORAN KEUANGAN? ANALISIS BENEISH RATIO INDEX: BERPERANKAH DALAM MENDETEKSI KECURANGAN PADA PELAPORAN KEUANGAN? - rafles ginting; Nicholas Christiansen; Ines Hanida; Julyanne Gracia Irawan (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study aims to determine the percentage of fraud in the financial reporting of construction companies, specifically WSKT and WIKA. Categorizing construction companies including manipulators, non-manipulators or gray companies from 2018-2022. The parameter index used is DSRI, GMI, AQI, SGI, TATA, DEPI, SGAI, and LVGI. The data collection method used is documentation. The population taken was 6 companies which used 5 annual financial data on each company so that the total was 30 data listed on the IDX. Data analysis uses descriptive quantitative analysis with the Beneish Ratio Index ratio. Data sources are obtained through the company's official website and the Indonesia Stock Exchange (IDX). The sample in the study used was purposive sampling. The results of this study indicate that the Beneish M-Score calculations of the two companies indicate manipulation of their financial reporting. The novelty of this research lies in the focus of research and the completeness of the Beneish M-Score calculation where researchers focus on WSKT and WIKA as the main point in the discussion where there is no research that focuses on the companies studied along with calculations that only use 5 calculations.